Research on the Way Right Control Technology forAutonomous-rail Rapid Transit - LIU Guangyong; SHI Yangyang; LIU Weikang; LIU Liu; JIA Bisheng; LUO Yunfeng; ZHANG Heng (Kongzhi Yu Xinxi Jishu)
The purpose of the way right control technology for autonomous-rail rapid transit (ART) is to study the technology of rational utilization of urban road resources while ensuring the operation efficiency of autonomous-rail rapid tram, based on the characteristics of limited, public and multiple intersections of urban road resources. From the perspective of rational use of road resources and public transport priority, this paper introduced the concept of right of way, then studied the operation of autonomous-rail rapid tram in the scenarios of segregated way right and integrated way right, and put forward a solution of "mobile right of way system + signal priority system at intersection", and explained the technical points needing to be focused on. This solution can ensure the operation efficiency of the autonomous-rail rapid tram and occupy the urban road resources as little as possible, and realize the improvement of the urban road transportation efficiency.